Study of poly (ethylene-co-vinyl acetate) as a self healing agent in geopolymer with exposure to various curing temperature - Yap, Sin Wee (2015)
Different studies have been done on the characteristics of fly ash based geopolymer concrete and yet there is quite less studies on the addition of self-healing agent to reduce the shrinkage phenomenon during heat curing. Reduction of pores percentage in the fly ash based geopolymer concrete was achieved via the addition of PVA (poly ethylene vinyl acetate) to fill up the pores during heat curing process. Fly ash based geopolymer in this research was the combination of fly ash (350kg/m3), fine aggregates (645kg/m3), NaOH solution (41kg/m3) and Na2SiO3 solution (103kg/m3). PVA was included at 1% of fly ash weight and subjected to heat curing of 60ºC, 70ºC and 90ºC for 24 h without any post-cast detainment period. This research has shown that PVA started to melt when temperature reach the melting point of PVA and filled the voids in fly ash based geopolymer concrete. The batch that undergoes 90 ºC heat curing showed lower void percentage and higher compressive strength than the other specimens cured with different temperatures. Conclusively, the results has revealed a new finding that addition of PVA with 90 ºC as the activation temperature could increase the compressive strength and decrease the void percentage in fly ash based geopolymer concrete.